The Geography Of Trade Relations Between The EU And The ENP Countries: Emerging Patterns And Policy Recommendations - George Petrakos; Dimitris Kallioras; Panagiotis Artelaris; Maria Tsiapa (European Regional Science Association (ERSA), 2013)
The European Neighborhood Policy (ENP), launched in 2004, is a unified EU policy framework towards the EU neighboring countries (ENP countries). The objective of the ENP is to strengthen the prosperity, stability and security of the (enlarged) EU and the ENP countries, creating a "ring of friends" around the EU. Currently, the ENP consists of two sub-groups; the ENP East (Armenia, Azerbaijan, Belarus, Georgia, Moldova and Ukraine) and the ENP South (Algeria, Egypt, Israel, Jordan, Lebanon, Libya, Morocco, Palestine, Syria and Tunisia). Even though the ENP is distinct from the process of EU enlargement, the ENP countries operate under conditions of "neighborhood Europeanization". This indicates a misfit between ENP demands, on the one hand, and ENP rewards, on the other. Given this misfit - and the concomitant skepticism about the ENP capacity to transfer EU values and rules to the neighboring countries - deep(er) economic (in particular, trade) integration between the EU economy and the ENP countries is considered to be a catalyst for the success of the ENP undertaking. The objective of the paper is to study the geography (i.e. the size, the composition and the direction) of EU-ENP trade, conducting an in-depth empirical analysis as regards the trade flows (i.e. imports and exports) of the EU and the ENP countries. The paper provides comparative empirical evidence concerning paths of trade integration between the EU and the ENP countries. It does so by undertaking a descriptive statistical and graphical analysis of the findings derived from the estimation of a series of trade indicators. The analysis utilizes trade data derived from the UN COMTRADE database. The analysis covers the period 2000-2010. This period has been selected so as to gauge the latest shifts operated in trade structures as a result of the recent economic and political reforms (evolutions) implemented (took place) in the EU economy (i.e. the euro currency, the eastwards enlargement, the on-going financial and economic crisis) and the ENP countries (i.e. the "color" revolutions, the Arab "spring"), besides the ENP in itself. Trade data refer to the national-sectoral (2-digit SITC classification) level. The sectors included in the analysis grossly belong to the primary and the secondary sector of production and may form groups of activities according to the intensity of the production factors used. Providing a clear picture regarding the geography of EU-ENP trade, the paper offers valuable insight to both (economic integration) theory and policy-making.
Keywords: 330; geography; trade; EU countries; ENP countries